Postprandial Insulin and Triglyceride Concentrations Are Suppressed in Response to Breaking Up Prolonged Sitting in Qatari Females - Chrismas, Bryna C. R.; Taylor, Lee; Cherif, Anissa; Sayegh, Suzan; Rizk, Nasser; El-Gamal, Abdelrahman; Allenjawi, Salwa Hassan; Bailey, Daniel P. (Frontiers in Physiology, 2019)
Background: Cultural, environmental and logistical factors challenge the Qatari population, particularly females, to engage in physical activity, and there is a high prevalence of diabetes in this population. Sedentary behaviour is associated with increased cardiometabolic disease risk and early mortality and breaking up sitting can attenuate postprandial cardiometabolic risk markers. However, no studies have evaluated the cardiometabolic response to breaking up sitting in a Qatari population. Purpose: To examine the effects of breaking up sitting with moderate-intensity walking breaks on cardiometabolic disease markers in Qatari females. Method: Eleven sedentary (sitting ≥7 h/day) females completed two experimental conditions in a cross-over randomised design. The two conditions were identical, except participants either remained seated for 5-h (SIT) or interrupted their sitting every 30-min with a 3-min walk (WALK) on a motorised treadmill (Rating of Perceived Exertion 12 – 14). A fasting venous blood sample was obtained at baseline (-10-min) followed by samples at 0.5-h, 1-h, 2-h, 3-h, 3.5-h, 4-h, and 5-h. Postprandial cardiometabolic variables (insulin, glucose, triglycerides) were calculated as derivatives of total area under the curve [AUC; total (tAUC), net incremental (iAUC) and positive AUC]. Results: Data is reported as effect size; ±90% confidence limit. There was a most likely ‘moderate’ lower tAUC (-0.92; ±0.26), iAUC (-0.96; ±0.33), and positive AUC (-0.96; ±0.33) for insulin in WALK compared to SIT. Additionally, there was a most likely ‘moderate’ lower tAUC (-0.63; ±0.37), iAUC (-0.91; ±0.49), and positive AUC (-0.91; ±0.49) for triglycerides in WALK compared to SIT. Glucose did not differ between conditions. Conclusion: Breaking up prolonged sitting with moderate-intensity walking offers a culturally and workplace compatible intervention to acutely improve cardiometabolic risk markers in sedentary Qatari females. Whilst the data offers promise, the long-term chronic effects of breaking up sitting in Qatari adults requires investigation before population level and/or policy recommendations can be made.